Molecular Typing of Australian Scedosporium Isolates Showing Genetic Variability and Numerous S. aurantiacum - Laurence Delhaes; Azian Harun; Sharon C.A. Chen; Quoc Nguyen; Monica Slavin; Christopher H. Heath; Krystyna Maszewska; Catriona Halliday; Vincent Robert; Tania C. Sorrell; Wieland Meyer (Emerging Infectious Diseases, 2008)
One hundred clinical isolates from a prospective nationwide study of scedosporiosis in Australia (2003–2005) and 46 additional isolates were genotyped by internal transcribed spacer–restriction fragment length polymorphism (ITS-RFLP) analysis, ITS sequencing, and M13 PCR fingerprinting. ITS-RFLP and PCR fingerprinting identified 3 distinct genetic groups. The first group corresponded to Scedosporium prolificans (n = 83), and the other 2 comprised isolates previously identified as S. apiospermum: one of these corresponded to S. apiospermum (n = 33) and the other to the newly described species S. aurantiacum (n = 30). Intraspecies variation was highest for S. apiospermum (58%), followed by S. prolificans (45%) and S. aurantiacum (28%) as determined by PCR fingerprinting. ITS sequence variation of 2.2% was observed among S. apiospermum isolates. No correlation was found between genotype of strains and their geographic origin, body site from which they were cultured, or colonization versus invasive disease. Twelve S. prolificans isolates from 2 suspected case clusters were examined by amplified fragment length polymorphism analysis. No specific clusters were confirmed.